Investigation of The Effect of Whole Pumpkin (Cucurbita pepo L.) Powder on Quality Criteria of Biscuits - Cem Baltacıoğlu; Nisanur Ülker (Turkish Journal of Agriculture: Food Science and Technology)
In this study, pumpkin (Cucurbita pepo L.), which is usually produced for its seeds, was used for production of whole pumpkin powder directly incorporated into biscuit formation. Fiber, protein and ash content of pumpkin powder are determined 13.4%, 8.5% and 4.7% (dry basis), respectively. Pumpkin powder was added into the dough by means of displacement with the wheat flour at rates of 15%, 30% and 45% during biscuit production. Firmness, work of shear, stickiness and work of adhesion were examined after adding pumpkin flour to biscuit dough at different rates and an increase of firmness, work of shear, stickiness and work of adhesion were recorded as 58.9%, 72.4%, 52.1%, and 29.4%, respectively. A decrease of 24.8% in thickness and 22.7% in volume were observed as the amount of pumpkin flour increases. When the color values were examined, darker biscuits were obtained compared to the control biscuit. Approximately an increase of 232.6% in ash content in biscuits was observed. Biscuits adding pumpkin powder had 58.4% more moisture content than the control biscuit. While decrease of hardness and toughness were observed as 82.3% and 85.4%, respectively, a significantly change of brittleness value was not observed. Biscuits were evaluated in the sensory analysis in terms of crust color, inner color, homogeneity and size of pore, taste, odor, softness, and dissolve in the mouth and greasy feeling in the mouth. According to the results of sensory analysis, biscuits that 45% pumpkin powder was added was the highest rated. According to the study, positive effects were obtained in terms of nutritional properties and favorable results were also found in texture and color of biscuits that pumpkin powder was added. These findings were also supported by the results of sensory analysis.